Development of Biomimetic Robots in the EPS Engineering Programme Capstone Project - Silva, Manuel (2015)
This paper proposes the development of biologically inspired robots as the capstone project of the European Project Semester (EPS) framework. EPS is a one semester student centred international programme offered by a group of European engineering schools (EPS Providers) as part of their student exchange programme portfolio. EPS is organized around a central module (the EPS project) and a set of complementary supportive modules. Project proposals refer to open multidisciplinary real world problems. Its purpose is to expose students to problems of a greater dimension and complexity than those faced throughout the degree programme as well as to put them in contact with the socalled real world, in opposition to the academic world. Students are organized in teams, grouping individuals from diverse academic backgrounds and nationalities, and each team is fully responsible for conducting its project. EPS provides an integrated framework for undertaking capstone projects, which is focused on multicultural and multidisciplinary teamwork, communication, problem-solving, creativity, leadership, entrepreneurship, ethical reasoning and global contextual analysis. The design and development of biologically inspired robots allows the students to fulfil the previously described requirements and objectives and, as a result, we recommend the adoption of these projects within the EPS project capstone module for the benefit of engineering students.